2012
DOI: 10.1097/njh.0b013e318243251f
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation in Change-of-Shift Procedures

Abstract: In the Italian health system, the most common handover model is that of a meeting between nurses at the shift change in the nurses' staff room. The information dealt with at the handover tends to cover patients' medical diagnoses, physical symptoms, and clinical events. Information tends to be omitted however, relating to patients' needs and their care plan, all elements that might benefit from involvement of the patient. This research, using Lewin's 3-Step Model for Change, tracks the change at an Italian hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…Nurses often just assume that this type of patients cannot or will not participate in their care (Lyttle & Ryan, 2010), therefore designating the bedside handover as not possible for patients of older age. The single study we identified (Wildner & Ferri, 2012) confirms this typical idea about elderly and the fact that patient participation was not mentioned in the other studies is perhaps a symptom of the same misunderstanding. As emphasised by Anderson and Mangino, patient participation is a crucial aspect of the bedside handover in order to achieve the beneficial effects.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Nurses often just assume that this type of patients cannot or will not participate in their care (Lyttle & Ryan, 2010), therefore designating the bedside handover as not possible for patients of older age. The single study we identified (Wildner & Ferri, 2012) confirms this typical idea about elderly and the fact that patient participation was not mentioned in the other studies is perhaps a symptom of the same misunderstanding. As emphasised by Anderson and Mangino, patient participation is a crucial aspect of the bedside handover in order to achieve the beneficial effects.…”
supporting
confidence: 73%
“…After systematic screening of 154 hits (Appendices 1 and 2), 22 articles were considered eligible or needed full-text screening to determine eligibility. Of these 22 articles, nine discussed the use of the bedside handover on a ward with an (partially) older population, of which only one study (Wildner & Ferri, 2012) addressed the issue of patient participation. This study (Wildner & Ferri, 2012) had a small sample of both nurses (n = 12) and patients (n = 15), used a non-validated questionnaire, and mainly looked at the issue from the nurses perspective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Categoría I: Características de la entrega A la cabecera del paciente Algunos autores mencionan como una parte esencial para el recibo y entrega de turno, también identificado como paso de guardia, que este se debe realizar a la cabecera del paciente y con la participación del mismo, dicha entrega de turno consiste en una relación establecida enfermera(o)-paciente, donde el paciente comprende, busca y mantiene un sentido de control y reconocimiento de su propia responsabilidad frente a su estado de salud, mientras que enfermería actúa para facilitar este papel y proporciona información ajustada a las necesidades de cada individuo. La metodología que plantean estos autores para la entrega de turno comprende a los dos equipos de enfermería (el turno de salida y el turno de entrada), quienes en conjunto pasan por las habitaciones de los pacientes, se detienen en sus camas e intercambian la información vital relacionada con su cuidado [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Discussionunclassified